- #1

stuck

- 6

- 0

**Prove the following identities:**

(cos A = cos B)^2 + (sin A + sin B)^2 = 2[1+cos(A-B)]

(cos A = cos B)^2 + (sin A + sin B)^2 = 2[1+cos(A-B)]

I'm really a mess at this stuff. I missed a few important days and fell behind, so I don't reeeally know what to do when things start getting squared and whatnot., but I tried!

*Left Side*

**(cos A + Cos B)^2 + (sin A + sin B)^2**

(cos(^2)A+cos(^2)B = Sin(^2)A+sin(^2)B

(cos (^2)A+cos(^2)B+ (1+-cos(^2)A + (1+-cos(^2)B)

2

(cos(^2)A+cos(^2)B = Sin(^2)A+sin(^2)B

(cos (^2)A+cos(^2)B+ (1+-cos(^2)A + (1+-cos(^2)B)

2

*Right Side*

**2+2cos(A-B)**

2(cosAcosB+sinAsinB) +2

2(cosAcosB+sinAsinB) +2

But that's as far as I can get. I can't find a way to make both sides equal, and I'm not even sure if my left side is correct...

Please help me if you can! :shy:

Last edited: